Genera resembling Beckerina Malloch (Diptera: Phoridae) - Disney, R. Henry L. (Zootaxa, 2004)
The addition of species to the genus Beckerina Malloch (1910) progressively eroded its diagnosis to the point that it became increasingly difficult to recognise its boundaries. An amended diagnosis is provided and three new genera proposed, along with the following new combinations for species formerly included in Beckerina. Brownphora sinefurca (Borgmeier) gen. nov., comb. nov., Enderleinphora fuscohalterata (Enderlein) gen. nov., comb. nov. and Mallochphora orphnephiloides (Malloch) gen. nov., comb. nov. Enderleinphora hansoni sp. nov. is described from Costa Rica.